Pengaruh Spiritual Leadership, Stres Kerja, dan Kompensasi Terhadap Kepuasan dan Prestasi Kerja Social Worker Organisasi Sosial di Surabaya (Jurnal Bimbingan dan Konseling Islam, 2013)
Social organization in Surabaya should apply appropriate leadership model, able to manage work stress members in fundraising tasks, and implement fair compensation policies to meet the expectations of the social worker and the organization itself . This study aimed to clarify the influence of spiritual leadership, work stress, job satisfaction and compensation for social worker and job performance. Analysis using Structural Equation Modeling (SEM) to examine the effect of directly or indirectly, the influence of the independent variable on the dependent variable. The size of the effect that occurs at a certain point would appear from the results of the calculation method of the SEM program AMOS (Analysis Of The Moment Structure). Sources of data obtained from social organizations excel in Surabaya by using proportional random sampling technique. The main instrument used in data collection is the questionnaire, while the supporting instruments were interviews, observation, and documentation. The analysis showed that there are several variables hypothesized in seven hypotheses have significant effects with positive relationships and partly direction has no significant effect with the negative direction of the relationship. Contribution of research in management theory, the focus on human resource management (HRM) is the need for compatibility between the spiritual leadership, job stress, non-financial compensation, job satisfaction, and job performance. Important findings in the study suggest that job satisfaction on job performance has the greatest level of significance, while the non-financial compensation has the most significant influence on job performance.Keywords : Spiritual Leadership, Work Stress, Non Financial Compensation, Job Satisfaction, Job Performance